Rebleeding and bleeding in the year following intracranial aneurysm coiling: analysis of a large prospective multicenter cohort of 1140 patients—Analysis of Recanalization after Endovascular Treatment of Intracranial Aneurysm (ARETA) Study - Pierot, Laurent; Barbe, Coralie; Herbreteau, Denis; Gauvrit, Jean-Yves; Januel, Anne-Christine; Bala, Fouzi; Ricolfi, Frédéric; Desal, Hubert; Velasco, Stéphane; Aggour, Mohamed; Chabert, Emmanuel; Sedat, Jacques; et al. (Journal of neurointerventional surgery, 2020)
BackgroundEndovascular treatment is the first line therapy for the management of ruptured and unruptured intracranial aneurysms, but delayed aneurysm rupture leading to bleeding/rebleeding can occur subsequently. ARETA (Analysis of Recanalization after Endovascular Treatment of intracranial Aneurysm) is a prospective, multicenter study conducted to analyze aneurysm recanalization. We analyzed delayed bleeding and rebleeding in this large cohort.Methods16 neurointerventional departments prospectively enrolled patients treated for ruptured and unruptured aneurysms between December 2013 and May 2015 (ClinicalTrials.gov: NCT01942512). Participant demographics, aneurysm characteristics and endovascular techniques were recorded. Data were analyzed from participants with ruptured or unruptured aneurysms treated by coiling or balloon-assisted coiling. Rates of bleeding and rebleeding were analyzed and associated factors were studied using univariable and multivariable analyses.ResultsThe bleeding rate was 0.0% in patients with unruptured aneurysms and 1.0% (95% CI 0.3% to 1.7%) in patients with ruptured aneurysms. In multivariate analysis, two factors were associated with rebleeding occurrence: incomplete aneurysm occlusion after initial treatment (2.0% in incomplete aneurysm occlusion vs 0.2% in complete aneurysm occlusion, OR 10.2, 95% CI 1.2 to 83.3; p=0.03) and dome-to-neck ratio (1.5±0.5 with rebleeding vs 2.2±0.9 without rebleeding, OR 0.2, 95% CI 0.04 to 0.8; p=0.03). Modalities of management of aneurysm rebleeding as well as clinical outcomes are described.ConclusionsAneurysm coiling affords good protection against bleeding (for unruptured aneurysms) and rebleeding (for ruptured aneurysms) at 1 year with rates of 0.0% and 1.0%, respectively. Aneurysm occlusion and dome-to-neck ratio are the two factors that appear to play a role in the occurrence of rebleeding.